Evaluation of an Enhanced Recovery After Surgery Protocol Including Parasternal Intercostal Nerve Block in Cardiac Surgery Requiring Sternotomy. Issue 10 (October 2021) - Abadi, Arad; Cohen, Robbin
Background: Recent guidelines for perioperative care in cardiac surgery recommend multimodal pain management to decrease opioid use. We evaluated the effect of multimodal pain management including parasternal intercostal nerve block on pain control and opioid use in patients who underwent coronary artery bypass grafting (CABG) requiring sternotomy and cardiopulmonary bypass. Study Design: Medical records of consecutive patients who underwent CABG from 2018 to 2019 at Huntington Hospital were retrospectively queried. Patients were divided in 2 groups based on whether an Enhanced Recovery After Surgery (ERAS) pain management protocol including parasternal intercostal nerve blocks was employed. Outcomes, including length of stay, pain scores, and opioid use, were compared. Results: There was no difference in length of stay (days) 5.43 vs. 5.38 ( P = .45 and average pain score 2.23 vs. 3.27 ( P = .137) for patients in the ERAS and non-ERAS groups. Maximum pain score, 7.74 to 6.15 ( P = .015), and opioid use (total morphine mg equivalent), 149.64 to 32.01 ( P < .01), were reduced in the ERAS group. Conclusion: The ERAS multimodal pain management protocol utilizing intraoperative parasternal blocks appears to reduce pain and decrease opioid use after CABG.